Prospective approaches to enhancing CAR T cell therapy for glioblastoma - Choi, Sun Il; Yin, Jinlong (Frontiers in Immunology, 2022)
Glioblastoma (GBM) is the most common malignant brain tumor. The poor clinical outcome and overall ineffectiveness of current standard treatments, including surgery, chemotherapy, and radiation, highlight the urgent need for alternative tumor-specific therapies for GBM. Chimeric antigen receptor T (CAR T) cell therapy is a revolutionary therapeutic strategy for hematological malignancies, but the optimal potency of CAR T cell therapy for solid tumors, especially GBM, has not been achieved. Although CAR T cell therapeutic strategies for GBM have been assessed in clinical trials, the current antitumor activity of CAR T cells remains insufficient. In this review, we present our perspective on genetically modifying CAR constructs, overcoming T cell dysfunctions, and developing additional treatments that can improve CAR T cell effectiveness, such as functionality, persistence, and infiltration into tumor sites. Effectively improved CAR T cells may offer patients with GBM new treatment opportunities, and this review is intended to provide a comprehensive overview for researchers to develop potent CAR T cells using genetic engineering or combinatorial preparations.